IDEOLOGICAL ARTISTIC FEATURE OF NOVEL OF LEONID MOSENDZ «THE LAST PROPHET» - Maftyn , N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the question is ideological artistic features to the novel of Leonid Mosendz « The Last Prophet» (on Ukraine the work was published during 1994-1995 in a magazine «Dnepr»). Influence of world view dominant is considered on forming of conception of work and its realization in the artistic measuring of text.